The phylogeny of nine species of the Drosophila obscura group inferred by the banding homologies of chromosomal regions: 11. Element E - Brehm, António (2020)
The phylogenetic relationships among nine species of Drosophila belonging to the obscura group were investigated by establishing (according to their banding similarities) the homologous chromosome segments of element E (equivalent to chromosome O of D. subobscura). The phylogenetic relationships were based on the existence of segments in different triads of species, which could only be produced by overlapping inversions. This permitted the ordering of the species belonging to each triad. Drosophila obscura, D. ambigua and D. tristis were found to be very closely related and thus forming a cluster in which D. ambigua occupies an intermediate position between the other two species. Drosophila obscura seems to be the species more directly linked to three other separate lineages, that of D. subsilvestris, the two African species (D. microlabis and D. kitumensis), and the subobscura cluster. The species from this last cluster may be ordered as follows: D. subobscura-D. madeirensis-D. guanche. It is not clear which species of this triad is the direct link to D. obscura. These results completely agree with those produced in an independent study, where element B was considered for the same nine species. Furthermore, the present study clarifies some ambiguities concerning the phylogenetic relationships which remained obscure due to the conservative nature of chromosome B.